Studi Kualitatif Dinamika Motivasi Belajar Matematika Siswa Kelas III Melalui Penggunaan Media Ular Tangga - Siti Nurhaliza SR; Nuryami; Nur Khosiah (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2026)
The purpose of this study was to investigate the dynamics that influence students' motivation to learn mathematics when using snakes and ladders in third grade.  The background of this study was based on low student motivation and learning outcomes, especially in mathematics, which is usually considered difficult and boring.  This study was conducted using a qualitative approach and case studies.  At one elementary school, observations, interviews, and documentation were conducted to collect data. The results showed that using snakes and ladders media when teaching mathematics can increase student engagement and enthusiasm.  Through a fun and interactive approach, this media encourages students to be more active, ask questions, and better understand the material. This media can also help students with different learning styles and create a more lively and supportive classroom atmosphere.  In addition, students have higher intrinsic motivation, as shown by their desire to learn more and complete tasks independently. Thus, it can be concluded that educational games such as snakes and ladders are effective in increasing students' motivation to learn and improving their understanding of mathematical concepts in elementary school. This study suggests the use of interactive and creative media as an alternative learning approach that supports a more effective teaching and learning process.